A comparative experimental investigation on thermal performance for two types of vacuum tube solar air collectors based on flat micro-heat pipe arrays (FMHPA). (1st May 2020) - Wang, Tengyue; Diao, Yanhua; Zhao, Yaohua; Liang, Lin; Wang, Zeyu; Chen, Chuanqi
Highlights: Conventional-tube and transparent-tube solar air collectors are designed. Selective absorption coatings are located at different places. A large air volume flow rate contributes to a high efficiency. Collector efficiency of transparent-tube is larger than that of ordinary-tube. Conventional-tube collector has advantages of heating capability and economy. Abstract: Two types of solar air collectors (SACs), namely, a conventional-tube collector (C-TC) and a transparent-tube collector (T-TC), are designed on the basis of flat micro-heat pipe arrays (FMHPA) and are compared. FMHPA is used as the core heat transfer element for both collectors. Absorption coatings are located at different places. It is located at, namely, on the inner wall of vacuum tube and on the FMHPA evaporation section in the C-TC and the T-TC. A large volumetric flow rate of air contributes to high efficiency. Results of the comparative experiment show that even if the thermal efficiency of the C-TC (77.6%) is smaller than that of the T-TC (85.0%), the useful energy of the C-TC (641 W) is larger than that of the T-TC (497 W). Moreover, the COP values of the C-TC and T-TC are 11.4 and 8.9, respectively. The unit initial investments are 0.15 and 0.21 $/W. Hence, considering the heating capability and price advantage, the C-TC is a better collector form than the T-TC in the same collector gross area. The collector pressure drop does not exceed 19.1 Pa. These results can serve as a reference for the selection and design of SACs for heating applications and crop drying.